2022
DOI: 10.3390/biom12020156
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin: Not Just Another Gastrointestinal Peptide

Abstract: Adrenomedullin (AM) and proadrenomedullin N-terminal 20 peptide (PAMP) are two bioactive peptides derived from the same precursor with several biological functions including vasodilation, angiogenesis, or anti-inflammation, among others. AM and PAMP are widely expressed throughout the gastrointestinal (GI) tract where they behave as GI hormones, regulating numerous physiological processes such as gastric emptying, gastric acid release, insulin secretion, bowel movements, or intestinal barrier function. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 158 publications
(245 reference statements)
1
6
0
Order By: Relevance
“…This reinforces the inverse association of ADM with the PhA, as a lower PhA is related to higher fluid overload (higher ECF/ICF) relative to BCM [1]. Next to volume overload [40], other stimuli of ADM synthesis are inflammation-related markers [41], which can induce cell damage, while cell damage can initiate inflammation [42], potentially decreasing the PhA.…”
Section: Selected Protein Markers Associated With the Phasupporting
confidence: 63%
“…This reinforces the inverse association of ADM with the PhA, as a lower PhA is related to higher fluid overload (higher ECF/ICF) relative to BCM [1]. Next to volume overload [40], other stimuli of ADM synthesis are inflammation-related markers [41], which can induce cell damage, while cell damage can initiate inflammation [42], potentially decreasing the PhA.…”
Section: Selected Protein Markers Associated With the Phasupporting
confidence: 63%
“…However, it can be hypothesized that the protective factors of milk components are diminished when components are reduced or eliminated through storage and feeding practices. For example, adrenomedullin (AM) is a hormone in the gastrointestinal (GI) tract present in human milk [32]. Within the GI tract, AM is known to help regulate many physiological processes, including anti-inflammation, organ protection, tissue repair, and improved intestinal barrier function [32].…”
Section: Potential Benefits Of Fresh Parent's Own Milk To Infant Heal...mentioning
confidence: 99%
“…The protein encoded by this gene is a preprohormone that is cleaved to form two biologically active peptides, adrenomedullin and proadrenomedullin N-terminal 20 peptide. Adrenomedullin is a bioactive peptide consisting of 52 amino acids ( 107 ) that possesses a variety of biological functions, including vasodilation, regulation of hormone secretion, promotion of angiogenesis, and antimicrobial activity ( 108 111 ). Previous studies have shown that AM and its receptors are highly expressed in the uterus and placenta, especially in the fetal membranes and umbilical cord blood vessels, which could relax the placental blood vessels in a dose-dependent manner through autocrine or paracrine forms and reduce the resistance of placental blood vessels ( 112 , 113 ).…”
Section: Approaches To Establish the Pas Modelmentioning
confidence: 99%